(untitled) (Research, Society and Development, 2021)
Objective: to analyze the knowledge and attitudes of the nursing team to promote neonatal thermoregulation. Method: 11 semi-structured interviews were conducted in November/December 2020, with members of the maternity nursing team of a University Hospital, later submitted to thematic analysis and categorized into two thematic units entitled: team knowledge and team attitudes. Results: a knowledge gap was perceived between technical professionals and nurses on the subject. The participants were able to correctly elucidate the clinical repercussions of inadequate thermoregulation, and cited the material resources available to promote it, such as heated cradle and incubator. Regarding nursing care, especially bathing, it was noticed that the team follows the recommendations of the World Health Organization and Ministry of Health, but these were belatedly implemented in the maternity ward. Conclusion: most attitudes corroborate the most current recommendations for the promotion and maintenance of the thermoregulation of the neonate.